A case of disseminated nontuberculous mycobacteriosis and cerebellar toxoplasmosis with autoantibody to interferon-γ - Yamaguchi, Etsuro; Tanaka, H.; Fukuoka, Takaaki; Ohbayashi, Y.; Sato, M.; Yokoi, T. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Autoantibody against interferon-γ has recently been associated with a variety of opportunisticinfections, particularly among Asians. We report the case of a 64-year-old Japanese woman who suffered from concomitant or sequential infections of the skin, lungs, bronchi, uterus, andbladder with nontuberculous mycobacteriosis, cerebellar toxoplasmosis, measles,herpes zoster, and vulvar herpes. Blood mononuclear cells from the patient displayed intact cytokine production in response to various stimuli and interferon-γ. High-titer anti-interferon-γ autoantibodies were detected in her serum. The atypical pathology hampered early diagnosis, but indeterminate results of an interferon-γ release assay could offer a simple clue suggesting the presence of autoantibody.